Pengembangan E-Modul Berbasis Problem Based Learning pada Materi Sistem Pernapasan untuk Meningkatkan Hasil Belajar Kognitif Siswa SMP - Romawani Waruwu; Nirwana Anas; Rohani Rohani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
The effectiveness of use of printed teaching materials such as student textbooks, such as textbooks, opens up opportunities for integrating a teaching material supplement with the latest information technology to support the achievement of 21st century skills. One of them is the development of an e-module based on Problem Based Learning. This research aims to develop valid, practical, and effective Problem Based Learning e-modules. This research uses research and development methods with the 4D development model (Define, Design, Develop, and Disseminate). The test subjects in this study were class VIII students of SMP Muhammadiyah 17 Pon Village, Sei Bamban District, Serdang Bedagai Regency, North Sumatra Province. The results showed that: 1) the validation results of media experts obtained an average percentage of 77.63% in the valid category. The results of the material expert validation obtained an average percentage of 97.61% with a very valid category. The results of the linguist validation obtained an average percentage of 100% with a very valid category; 2) the results of the teacher's response assessment obtained an average percentage of 81.06% in the very practical category. The results of assessing the responses of students in the small group tryout obtained an average percentage of 87.22% in the very practical category, and in the large group tryout an average percentage of 87.84% was obtained in the very practical category; and 3) product effectiveness test using the N-gain test obtained an average score of 0.59 indicating an increase in cognitive learning outcomes with moderate criteria. Based on the results of testing the validity, practicality and effectiveness of the product, the e-module based on Problem Based Learning on respiratory system material developed is valid, practical and effective for teachers and students to use in the process of learning natural sciences.